2017
DOI: 10.1371/journal.pbio.2001644
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput identification and rational design of synergistic small-molecule pairs for combating and bypassing antibiotic resistance

Abstract: Antibiotic-resistant infections kill approximately 23,000 people and cost $20,000,000,000 each year in the United States alone despite the widespread use of small-molecule antimicrobial combination therapy. Antibiotic combinations typically have an additive effect: the efficacy of the combination matches the sum of the efficacies of each antibiotic when used alone. Small molecules can also act synergistically when the efficacy of the combination is greater than the additive efficacy. However, synergistic combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 92 publications
3
59
0
1
Order By: Relevance
“…[17,18] Target-based whole-cell screenings include comparative profiling of,f or example,g enetically modified versus wildtype bacterial strains or the rescue of an antibiotic effect upon external supplementation, for example,o fametabolite. [105][106][107][108][109] Numerous HTS campaigns have been performed in various genetically modified E. coli reporter strains.…”
Section: Screening Platformsmentioning
confidence: 99%
See 1 more Smart Citation
“…[17,18] Target-based whole-cell screenings include comparative profiling of,f or example,g enetically modified versus wildtype bacterial strains or the rescue of an antibiotic effect upon external supplementation, for example,o fametabolite. [105][106][107][108][109] Numerous HTS campaigns have been performed in various genetically modified E. coli reporter strains.…”
Section: Screening Platformsmentioning
confidence: 99%
“…Bioinformatic approaches aim to take advantage of these huge data sets to identify new antibacterial compounds and potential new targets or to help clarify the mode of action of new compounds. [105][106][107][108][109]…”
Section: Screening Platformsmentioning
confidence: 99%
“…We showed that identifying these drug interactions can quickly lead to additional interacting pairs by examining structure (Fig. S3) or by investigating underlying mechanism (Wambaugh et al, 2017). Finally, our newly discovered interaction of dicyclomine and FLZ exhibited therapeutic potential in vivo, demonstrating the clinical potential of fluconazole-containing synergistic pairs in the clinic.…”
Section: Discussionmentioning
confidence: 82%
“…Synergistic combination therapies are increasingly important clinical options, especially for drug resistant microbes (Cowen and Lindquist, 2005;Kalan and Wright, 2011;Uppuluri et al, 2008;Zheng et al, 2018). Traditionally, synergistic drug pairs were discovered serendipitously, but new methods are improving our ability to uncover important interactions (Brown et al, 2014;Cokol et al, 2011;Cokol et al, 2018;Jansen et al, 2009;Robbins et al, 2015;Spitzer et al, 2011;Wambaugh et al, 2017;Wildenhain et al, 2015). In this study, we identified a wide variety of molecules that interact synergistically with the antifungal FLZ to inhibit fungal growth.…”
Section: Discussionmentioning
confidence: 86%
“…Bioinformatische Methoden haben das Ziel, diese großen Datensätze zu nutzen, um neue antibakterielle Verbindungen und potentielle neue zelluläre Targets zu identifizieren oder den Wirkmechanismus von neuen Verbindungen aufzuklären. [105][106][107][108][109]…”
Section: Screening-plattformenunclassified